The reality of the practice of digital citizenship by secondary school leaders in Riyadh and the requirements for its activation in the light of the European experience from their point of view - Al-Ghamdi, Afaf Othman; Al-Arifi, Hessa Saad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of the practice of digital citizenship by secondary school leaders in the Riyadh region and the requirements for its activation in the light of the European experience from their point of view. A stratified random sample of (232) school leaders was chosen. with an overall average (3.50 out of 5); to a (significant) degree, and as for its fields; Digital access obtained the highest average (3.37), then illiteracy (4.22), both with a (very large) degree. Thirdly, health and safety (4.01), and fourthly; Fitness (3.93) Fifth; connections (3.67) and finally; Rights and Responsibilities (3.54), all of which are rated (high), and the axis of the requirements for activating digital citizenship received an overall average of (4.57) with a (very large) degree. The degrees of the study sample on the role of digital citizenship among female leaders of general education schools at the secondary stage in the light of the European experience, which is attributed to the academic qualification, while there is a statistically significant difference between the sample members according to the following variables: (years of educational experience in the axis of the reality of digital citizenship, and in favor of whom Their years of experience are 10 years or more, and according to training programs in the axis of digital citizenship challenges and for the benefit of individuals who did not receive training programs in the light of the results of the study, a proposed vision was developed to activate the role of digital citizenship in the light of the European experience.